Generation mean analysis for yield and grain quality traits in rice (Oryza sativa L. ) - Amardeep Kour; Bupesh Kumar; Bikram Singh; Heena Attri and; Sandeep Kumar Bangarwa (Electronic Journal of Plant Breeding, 2019)
Three cross combinations each having P1, P2, F1, F2, BC1 and BC2 were evaluated in Compact Family Block Design with three replications to estimate the genetic parameters. Analysis of variance revealed significant differences among generations in all the characters studied except grain breadth in all the three crosses, and kernel length after cooking in cross III. The significance of scaling tests (A, B, C and D) indicated appreciable amount of epistasis present in different characters of three cross combinations under study, indicating the failure of a simple genetic model to explain the genetic system controlling the traits except grain breadth in all the three cross combinations and grain length/breadth ratio in cross combination II.